HUBUNGAN HASIL ANALISIS GRAFOLOGI DENGAN HASIL BELAJAR PRAKTIKUM ZOOLOGI INVERTEBRATA MAHASISWA ANGKATAN 2013 JURUSAN PENDIDIKAN BIOLOGI FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - Mustafiah Mustafiah; Sitti Syamsudduha; Umi Kusyairi; Putro Perdana (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2017)
This research discusses the relationship between graphology analysis results and the results of student learning lab of Invertebrate Zoology. The problems of this research that is how the image of graphology analysis of student results, how the image of Invertebrate Zoology lab learning outcomes of students and whether there is a relationship between graphology analysis results with the learning outcomes of Invertebrate Zoology lab. The purpose of this study is to describe the student graphology analysis results, to describe the learning outcomes of Invertebrate Zoology practicum students and to determine whether there is a relationship between the results of graphology analysis of the learning outcomes of Invertebrate Zoology studentpracticum.This research is a correlational study. Research is done in the laboratory of Biology Education and Teaching Faculty of MT, UIN Alauddin Makassar. The population in this study were all students of the Department of Biology force in 2013, amounting to 115 people with a sample of 29 (25%). To obtain data on graphology analysis results, this study uses the full report of Invertebrate Zoology lab as handwriting samples of students were analyzed using graphology assessment instruments. While data on practicum learning outcomes, used assessment instruments of practicum. Data analysis technique used is descriptive and inferential statistics.Graphology analysis results obtained by the average value of 57.4 in the medium category. Practicum learning outcomes obtained by the average value of 65.7 in middle category. The results of inferential statistical analysis with Pearson product moment correlation r value of 0.928 was obtained which showed there was a significant relationship between graphology analysis results with the results of student learning lab.